Fine particulate matter and cause-specific mortality in the Hong Kong elder patients with chronic kidney disease. (May 2020) - Ran, Jinjun; Sun, Shengzhi; Han, Lefei; Zhao, Shi; Chen, Dieyi; Guo, Fang; Li, Jinhui; Qiu, Hong; Lei, Yujie; Tian, Linwei
Abstract: Emerging epidemiologic studies suggested that particulate matter (PM) was a risk factor for the incidence of chronic kidney disease (CKD). However, few studies were conducted to examine whether PM was associated with cause-specific deaths in the CKD progression. This study aimed to estimate the association between fine particulate matter (PM2.5 ) and a spectrum of deaths among CKD patients. We took leverage of the Elderly Health Service cohort (n = 66, 820), a large Hong Kong elderly cohort followed up till 2010. A total of 902 CKD incident patients in the cohort were identified during the follow-up period. We estimated yearly PM2.5 at the residential address for each CKD patient based on a satellite-based spatiotemporal model. We used Cox proportional hazards models with attained age as the underlying timescale to assess the association between long-term exposure to PM2.5 and cause-specific mortality among CKD patients. A total of 496 patients died during the follow-up, where 147 died from cardiovascular disease, 61 from respiratory disease and 154 from renal failure. The mortality hazard ratio (HR) per interquartile-range increase in PM2.5 (4.0 μg/m 3 ) was 1.97 (95% confidence interval (CI): 1.34 to 2.91) for ischemic heart disease (IHD) among CKD patients, and was 1.42 (95%CI: 1.05 to 1.93) for CKD among those patients concomitantly with hypertension. Associations were not of statistical significance between PM2.5 and mortality hazard ratios of all-cause, stroke, and pneumonia among CKD patients. Our findings suggest that long-term exposure to PM2.5 may contribute to the CKD progression into ischemic heart diseases. Highlights: Evidence is limited on cause-specific mortality HRs with PM2.5 among CKD patients. Long-term exposure to PM2.5 may increase the mortality HR of IHD among CKD patients. PM2.5 was associated with renal failure mortality among patients with hypertension. Associations with all-cause, stroke and pneumonia mortality were not significant.